Crop formation and green mass quality of maize under the conditions of central agroclimatic region of Komi Republic - G. N. Tabalenkova; E. V. Silina; O. V. Dymova; I. V. Dalke; T. K. Golovko (Аграрная наука Евро-Северо-Востока, 2021)
In the field experiment on the area of 100 m2 the impact of weather conditions on green mass formation and chemical composition of early ripe three-line maizehybrid DorkaMGT grown in the central agroclimatic region of the Komi Republic was studied. According tothe data of three vegetation seasons (2018-2020), the maize plants can form up to 56.5 t/ha green mass in the northern non-black earth region withthe sum of average daily active temperatures over 10 °C (GDD10) of about 1500 °C and a hydrothermal coefficient (HTC) of about 2. The decrease in GDD10 of 30 % and moderate precipitation (HTC = 2.3) resulted in a proportional decrease in green mass yield. During the growing season with abundant precipitation (HTC = 4), the production potential efficiency of maize plants fell significantly as evidenced by a decrease in yield by more than 4 times. The average yield of green mass over 3 years was 35.5 t/ha. No significant effects of vegetation conditions on the content of basic chemical elements and nutrients (sugars, protein) in plant biomasshave been revealed. The rate of visible photosynthesis of maize leaves reached 13-14 pmol CO2 / (m2s) during the period of intensive vegetative growth (phase of five leaves) and decreased during the transition to generative development (“heading of panicle” phase). In general, the data obtained indicate the possibility of growing early ripe maize hybrid Dorka MGT in the central agroclimatic region of the Komi Republic to obtain high-quality green feed and silage.